IPEx: A gamification tool for learner application of pharmacologic principles of opioid use, misuse, and addiction - Kelly Karpa; Josie Ward; Melanie Stegman; Arthur Berg; Shou Ling Leong (Wiley, 2023)
Abstract Opioids are often prescribed to treat chronic pain ailments, despite lack of evidence for many conditions. Prescriptions frequently become the gateway to opioid misuse and abuse. In response to the opioid crisis, medical school educators in the state of Pennsylvania developed core competencies pertaining to opioids and addiction for which all medical students should demonstrate proficiency before graduation. To enable students to achieve these competencies, we developed a web‐based app (IPEx) that delivers a gamified experience for learners in which they are (re)exposed to opioid competencies and practice applying pharmacologic principles in the context of a series of longitudinal patient scenarios. Learning and application are measured by student responses to application questions before and after each of five modules. Prior to launching the IPEx tool broadly, we wished to test the application questions; thus, we invited fourth year medical students to complete a 45 question quiz based on IPEx module content. Students had no specific preparation prior to taking the quiz but had been exposed to all content elsewhere in the curriculum. A total of 45 of 141 medical students (32%) opted to complete the quiz (mean score was 47% ± 13%; range 18%-73%). Cronbach alpha for the instrument was .74. These results suggest that the instrument has internal validity, and medical students have room for growth when it comes to application of opioid related competencies, a situation that the IPEx tool may be uniquely suited to remedy.